46 PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS MELALUI KEPUASAN PASIEN PENGGUNA BPJS DI RAWAT INAP RSUD Dr. MOEWARDI - Fitriani, Sri; Trisnawati, Rina (Universitas Muhammadiyah Surakarta, 2015)
Quality of service is a form of service provided by service providers, in this case the hospital, the quality of these services will have an impact on patient satisfaction and loyalty. This study aims to analyze the impact of service quality on patient loyalty, analyzing service quality on satisfaction, analyzing the effect of satisfaction on loyalty through the use of patient satisfaction BPJS. This research is descriptive and analytical, research in hospitals where Dr. Moewardi by taking a sample of 100 patients BPJS use. Data analysis techniques used by path analysis. The results showed: The quality of service has an influence on loyalty (p-value = 0.000), quality of service has an influence on loyalty (p-value = 0.000), patient satisfaction has an influence on loyalty p-value = 0.010), quality of service has not mengaruh directly to the loyalty of patients through patient satisfaction (p-value = 0.275).